Kinetics of Polymerization of Acrylamide initiated by p-Nitrophenyl Carbethoxy Azomethylen Triphenyl Phosphorane - Ji Shukla, Ram (Asian Journal of Chemistry, 2010)
Initiation of the polymerization of acrylamide (AM) by p-Nitrophenyl carbethoxy azomethylene triphenyl phospherane (p-NPCATP) in tetrahydrofuran-acetic-acid solution (1 : 9) has been studied kinetically at 65ºC using dilatometric technique. Initiator and the monomer exponent values were 0.6 and 0.9 respectively. Energy of activation was 38.32 KJ mol–1 and the value at kp2/kt was found to be 1.9 x 10–1 L mol–1 S–1. Polymerization was inhibited in the presence of hydroquinone. The results are explained in terms of radical mode of polymerization with bimolecular mode of termination.